Autoimmune Hemolytic Anemia and Immune Thrombocytopenia: A Unique Presentation of Kawasaki Disease - Kupelian, Chloe; Sathi, Bindu; Singh, Deepika (Case Reports in Rheumatology, 2021)
Kawasaki disease is an acute multisystem vasculitis characterized by involvement of medium-sized vessels that mostly affects children under the age of 5 years. The presentation is typically preceded by five or more days of fever with additional clinical findings including rash, peripheral edema, mucositis, conjunctival changes, and unilateral cervical lymphadenopathy. The most feared complication of Kawasaki disease is development of coronary artery aneurysms. Common laboratory abnormalities include normocytic anemia, thrombocytosis, leukocytosis, and elevated inflammatory markers. Immune-mediated cytopenias such as autoimmune hemolytic anemia and thrombocytopenia are rarely seen at presentation in Kawasaki disease. We describe a unique case of a child presenting with autoimmune hemolytic anemia, who sequentially developed immune thrombocytopenia concerning for Evans’ syndrome and eventually diagnosed with Kawasaki Disease with coronary artery dilatation. Characteristic clinical findings including extremity edema, cracked lips, and rash developed later in the course. Our patient was treated with IVIG and steroids with significant clinical improvement and complete resolution of cytopenias and coronary aneurysms on long term follow up. Timely administration of IVIG prevents and minimizes the risk of long term cardiac consequences. Hence a high index of suspicion should be maintained for this relatively common pediatric illness, even in absence of more commonly seen laboratory findings.